Usefulness of the 99mTc-MDP Scan in the Detection of Calcified Liver Metastases - Tokuue, K.; Furuse, M. (Nuklearmedizin - NuclearMedicine, 1990)
A 99mTc-MDP scan was done on a patient with liver metastases from a medullary thyroid carcinoma who, in addition, had a familial history of multiple endocrine neoplasm, type 2. The scan revealed accumulation in several areas of calcified liver metastases.Bei einem Patienten mit Lebermetastasen eines medullären Schilddrüsenkarzinoms wurde eine 99mTc-MDP- Skelettszintigraphie durchgeführt. Zusätzlich wies der Patient in der Familienanamnese eine multiple endokrine Neoplasie vom Typ 2 auf. Im Szinti- gramm wurde eine fokale Mehrspeicherung in mehreren verkalkten Lebermetastasen nachgewiesen.